Start młodzieży na rynku pracy - Nowak, Kazimierz (Przedsiębiorczość - Edukacja, 2007)
Poland belongs to the group of the poorest countries in European Union (country’s gross growth per capita according to the purchasing power constitutes about 45% of the union’s average). The development policy of our country should be based on the young and better educated people, on good perspectives for the development of enterprise, on scientific and cultural potential highly valued by the whole world and a continuously developing market. The fields in which the graduates of the universities may find good jobs in the future include: computer science, biotechnology, electrical engineering, English philology. National economic policy, stimulating the investments with good external effects and supporting the expansion of the knowledge based economy, contributes to the reduction of inequalities and the increase of social wealth. The inequalities lead to social losses and lower growth of the country’s profit. A mitigating the inequalities releases social energy used to fight against poverty and make people focus on the productive activities and initiatives. Young people should have better access to the job market. It is possible thanks to the creation a proper financial stimuli and a relevant system of adaptation to the market requirements.